Social Behavior of Mobile Legends Esport Athletes - Yuda Yudistira; Bangbang Syamsudar; Suhada (STKIP Pasundan Press, 2026)
This study aims to describe the social behavior of Mobile Legends esport athletes in the UKM Esport of STKIP Pasundan Cimahi. The research employed a descriptive qualitative method with photovoice and semi-structured interview approaches. The population consisted of 15 athletes, and five main team members were selected as samples using purposive sampling. Data were collected through photo documentation and interviews to describe the athletes' social behavior both within and outside the team. The results indicate that social behavior within the team is reflected in cooperation, emotional support, and strategic communication during practice and matches. Conversely, social behavior outside the team shows limitations in social interaction due to intensive and unstructured training patterns. The conclusion of this study is that high training intensity can restrict social interaction outside the team while strengthening social solidarity within it.